2007
DOI: 10.1007/s10584-007-9358-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on forest growth and tree mortality: a data-driven modeling study in the mixed-conifer forest of the Sierra Nevada, California

Abstract: We evaluated the impacts of climate change on the productivity and health of a forest in the mixed-conifer region in California. We adapted an industry-standard planning tool to forecast 30-years of growth for forest stands under a changing climate. Four projections of future climate (two global climate models and two emission forecasts) were examined for forests under three management regimes. Forest structural and tree demographic data from the Blodgett Forest Research Station in El Dorado County were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 36 publications
1
38
2
1
Order By: Relevance
“…In contrast, previous studies mostly evaluated impacts only for one time period e.g. 2050-2099 (Williams et al 2010) or over three time periods (Battles et al 2007). With respect to the emissions scenarios, our results emphasise increased changes in the drought risk particularly after the 2050s in accordance with higher emissions scenario uncertainty (Meehl et al 2007;Murphy et al 2009).…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…In contrast, previous studies mostly evaluated impacts only for one time period e.g. 2050-2099 (Williams et al 2010) or over three time periods (Battles et al 2007). With respect to the emissions scenarios, our results emphasise increased changes in the drought risk particularly after the 2050s in accordance with higher emissions scenario uncertainty (Meehl et al 2007;Murphy et al 2009).…”
Section: Resultscontrasting
confidence: 70%
“…1) similar to a study (Broadmeadow et al 2005) which incorporated additional limiting factors to tree growth and used previous non-probabilistic UK climate change projections (UKCIP2002). A study of drought impacts in the US showed a 25 % reduction in yield from pine plantations by 2100 (Battles et al 2007). With respect to time periods, we found a large yield class reduction of up to 89 % in the 2050s and even higher reductions up to 94 % by the 2080s.…”
Section: Resultsmentioning
confidence: 56%
“…In contrast, previous studies mostly evaluated impacts only for one time period e.g. 2050-2099 (Williams et al 2010) or over three time periods (Battles et al 2007). With respect to the emissions scenarios, our results emphasise increased changes in the drought risk particularly after the 2050s in accordance with higher emissions scenario uncertainty (Murphy et al 2009;Meehl et al 2007).…”
Section: Resultscontrasting
confidence: 70%
“…For oak, our results show a 13% reduction of the median stand yield class in the 2050s (Figure 3-1) similar to a study (Broadmeadow et al 2005) which incorporated additional limiting factors to tree growth and used previous UK climate change projections (UKCIP2002), but without probabilistic climate change data. A study of drought impacts in the US showed a 25% reduction in yield from pine plantations by 2100 (Battles et al 2007). With respect to time periods, we found a large yield class reduction of up to 89% in the 2050s and even higher reductions up to 94% by the 2080s.…”
Section: Resultsmentioning
confidence: 56%
“…Examples of these effects are shown for enhanced growth of Norway spruce (Picea abies) in forest productivity studies in Sweden and Finland [4]. However, negative effects have been observed on poor sites, decreasing growth [13] or increasing mortality of trees [14] especially under heat or drought stress [15], as a combined effect of temperature (increase) and precipitation (decrease).…”
Section: Impacts On Forest Growth and Productivitymentioning
confidence: 99%